Across the aisle : opposition in Canadian politics - Smith, David E., 1936-2023 (University of Toronto Press, 2013)
"How do parties with official opposition status influence Canadian politics? Across the Aisle is an innovative examination of the theory and practice of opposition in Canada, both in Parliament and in provincial legislatures. Extending from the pre-Confederation era to the present day, it focuses on whether Canada has developed a coherent tradition of parliamentary opposition.